An Empirical Impact Assessment of Antecedents and Enablers of Sustainable Project Management Implementation using a Structural Equation Modeling Approach - Qureshi, Salahuddin; Ali, Abid (Advanced and Sustainable Technologies (ASET), 2026)
This study examines the influence of key antecedents and enablers for the successful implementation of Sustainable Project Management (SPM). In emerging nations, organizations face challenges to integrate sustainability practices in the project life cycle due to the lack of integration of enabling factors. SPM is basically a new concept that seeks to align project objectives with social, environmental and economic benefits. In this study, the moderating effect of sustainability performance measurement and the mediating effect of sustainable project planning and technological advancement were thoroughly examined. A survey-based methodology was adopted to collect responses from project management professionals involved in project-based organizations. A total of 162 valid responses were analyzed, which is considered adequate for Partial Least Squares Structural Equation Modeling (PLS-SEM), given its suitability for small to medium sample sizes and complex models. The proposed hypotheses were tested using PLS-SEM techniques. The results show that antecedents and enablers had a significant impact on SPM implementation. The mediating effects of sustainable project planning and Technological advancement were found to be significant. However, the moderating effect of sustainability performance measurement was insignificant. The research concluded that incorporating sustainability into project management requires a holistic framework that accounts for both antecedents and enablers as key drivers. It also provides theoretical and practical implications for project practitioners to incorporate sustainability across various project life-cycle stages to improve project outcomes, which aligns with SDG 12 (Responsible Consumption and Production).